FUNGSI TARI KELANA GAYA SURAKARTA SUSUNAN S. NGALIMAN - Risang Janur Wendo (Institut Seni Indonesia Surakarta, 2014)
This paper aims to discover the function of the Kelana Dance created by S. Ngaliman bydescribing and explaining: (1) The form of the Kelana dance by S. Ngaliman, which includes itstheme, movements, masks, costumes, and music, and (2) Explaining the function of the Kelanadance by S. Ngaliman. The theoretical foundation which is used to uncover the function of theKelana dance by S. Ngaliman includes: (1) Theories of Performing Arts and (2) Theories of Function.The methods used by the writer for collecting the data required for addressing the problemthat had been formulated included: a library study, observation, interviews, and a transcriptionof documents and archives. Based on the form and function of the Kelana dance by S. Ngaliman inthe life of the community, it can be concluded that the Kelana dance is a solo male dance with astrong bapang character and a gandrungan(romantic) theme in Surakarta style, the primary functionof which is of an aesthetical nature and the secondary function of which is as part of awedding ritual, entertainment, and an educational tool.Keywords: Kelana mask dance, form, primary function and secondary function.